Kaposi's sarcoma-associated herpesvirus-infected primary effusion lymphoma has a plasma cell gene expression profile - Jenner, Richard G. (National Academy of Sciences, 2003)
Kaposi's sarcoma-associated herpesvirus is associated with three human tumors: Kaposi's sarcoma, and the B cell lymphomas, plasmablastic lymphoma associated with multicentric Castleman's disease, and primary effusion lymphoma (PEL). Epstein-Barr virus, the closest human relative of Kaposi's sarcoma-associated herpesvirus, mimics host B cell signaling pathways to direct B cell development toward a memory B cell phenotype. Epstein-Barr virus-associated B cell tumors are presumed to arise as a consequence of this virus-mediated B cell activation. The stage of B cell development represented by PEL, how this stage relates to tumor pathology, and how this information may be used to treat the disease are largely unknown. In this study we used gene expression profiling to order a range of B cell tumors by stage of development. PEL gene expression closely resembles that of malignant plasma cells, including the low expression of mature B cell genes. The unfolded protein response is partially activated in PEL, but is fully activated in plasma cell tumors, linking endoplasmic reticulum stress to plasma cell development through XBP-1. PEL cells can be defined by the overexpression of genes involved in inflammation, cell adhesion, and invasion, which may be responsible for their presentation in body cavities. Similar to malignant plasma cells, all PEL samples tested express the vitamin D receptor and are sensitive to the vitamin D analogue drug EB 1089 (Seocalcitol).